THE INFLUENCE OF WORK DISCIPLINE, POSITION PROMOTION AND WORK COMPETENCE ON EMPLOYEE PERFORMANCE IN PT SINDOMAS JAYA PERKASA - Rostina, Cut Fitri; Castello, David; Jonathan, Jerry; Anglhoma, Fietter; Romi, Mochamad Vrans (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2023)
This research was conducted at a metal distribution company, PT Sindomas Jaya Perkasa Medan. This study aimed to examine and analyze the influence of work discipline, promotion, and work competence on employee performance. This research method uses quantitative. The population of 178 employees and 123 employees is a sample of research. The sampling technique used is random sampling. Data analysis techniques using multiple linear regression analysis. The results of work discipline partially positive and significant effect on employee performance, promotion partially positive and significant effect on employee performance, work competence partially positive and significant effect on employee performance, and simultaneously work discipline, promotion, and work competence positively and significantly effect on employee performance.